2018
DOI: 10.1016/j.ijplas.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of micro slip and localization in polycrystalline materials under uniaxial tension

Abstract: Micro slip activation and localization in Ti-6Al-4V deformed in tension have been examined quantitatively using high-resolution (HR) digital image correlation (DIC), HR-electron backscatter diffraction (EBSD) and crystal plasticity finite element modelling. The measured polycrystal slip, strain, lattice rotation and geometrically necessary dislocation (GND) density distributions are generally well captured by the a priori crystal plasticity model based on the rate-sensitive properties of α-titanium. An overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 65 publications
4
36
0
Order By: Relevance
“…on Ti-6242 by Hemery(comparison) observed that most of the deformation was accommodated by individual soft grains with a Schmid factor above 0.4, but in both cases there was a non-negligible amount of slip occurring in grains with a Schmid factor of 0.2 to 0.4. [21,23] Every longrange slip trace from the present study has a basal Schmid factor above 0.4. It is interesting to note that Ti-6-4 only exhibits a dwell debit of about 2 to 3 times the LCF lifetime while Ti-6242 has a dwell debit of 10-20 times the LCF lifetime at room temperature when loaded to 90% of the macroscopic yield strength.…”
Section: Figure 5: Standard Deviation Of Basal Schmid Factor Per Slipmentioning
confidence: 71%
“…on Ti-6242 by Hemery(comparison) observed that most of the deformation was accommodated by individual soft grains with a Schmid factor above 0.4, but in both cases there was a non-negligible amount of slip occurring in grains with a Schmid factor of 0.2 to 0.4. [21,23] Every longrange slip trace from the present study has a basal Schmid factor above 0.4. It is interesting to note that Ti-6-4 only exhibits a dwell debit of about 2 to 3 times the LCF lifetime while Ti-6242 has a dwell debit of 10-20 times the LCF lifetime at room temperature when loaded to 90% of the macroscopic yield strength.…”
Section: Figure 5: Standard Deviation Of Basal Schmid Factor Per Slipmentioning
confidence: 71%
“…The evolution of the GND on interface has an effect on the formation of micro-defects and the thermal diffusion of solute. Moreover, the effect of GND [14,30] on meso-scale heterogeneous deformation of lamellar colony is very important. It is necessary to study the effect of GND on globularization of lamellar colony.…”
Section: Effect Of Geometry Necessary Dislocationmentioning
confidence: 99%
“…The thermal mechanical process is very sensitive to hotworking parameters and microstructure parameters, thus resulting in the difficulty in precisely controlling globularization. The detailed characteristics are described as follows: (a) complex and diverse morphologies (initial widmanstatten alpha [4], secondary alpha [28] and fine acicular martensitic alpha [29]) lead to the difference in globularization dynamics; (b) the meso-scale heterogeneous deformation (strain localization at lamellar-scale, strain partitioning behavior at colony-scale, macro-deformation bands at polycrystal-scale [15]); (c) the complex coupling effects of hot-working parameters and microstructure parameters (flow softening due to loss of interfacial coherency [3], evolution of geometry necessary dislocation(GND) at alpha/beta interface [29], the effect of lattice rotation [14,30] on meso-scale heterogeneous deformation). In general, an in-depth understanding of the effects of hot-working parameters and microstructure parameters can allow better control globularization of titanium alloy with lamellar colony.…”
Section: Introductionmentioning
confidence: 99%
“…Kapoor and co-workers 40,41 applied a similar method to study strain localization and residual stress of lamellar Ti6Al4V alloy. Although Euler angle data available from EBSD measurements has been used to define grain orientations in CPFE models 3,[42][43][44] , the comparative and quantitative benefits vis-à-vis artificially-generated (e.g. VT) models for FCI has not previously been addressed.…”
Section: Introductionmentioning
confidence: 99%